Remuneration of employee inventions at Czech universities - Svačina, Pavel; Rýdlová, Barbora; Boháček, Martin (Univerzita Pardubice, 2018)
Universities have recently been facing pressure to increase the share of commercialized R&D results, as well as to manage their intellectual property rights responsibly, including the remuneration of employee-inventors. The paper brings the first overall evidence of monetary incentives and rewarding schemes for employee inventors at Czech universities. The analysis is based on the data of 15 Czech public universities, which account for 98.7% of the patenting activity of all Czech universities. We perform a content analysis of their internal guidelines, explore and discuss how they interpret and apply key categories of broad legal framework defined by the Czech patent law. We found that each university complies formally with the law and has some remuneration system for employee inventors. Most of the schemes are combined, paying employees a certain initial reward and share in income from future technology commercialization. Although there is some common ground, we found many creative approaches across the sample in particular remuneration elements.
Keywords: employee inventions; monetary incentives; reward; royalty-sharing; patents; O31; O34; I23; J33; M52